2019
DOI: 10.3390/agronomy9120833
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Crop Tolerance to Heat and Drought—A Deep Convolutional Neural Networks Approach

Abstract: Environmental stresses such as drought and heat can cause substantial yield loss in agriculture. As such, hybrid crops that are tolerant to drought and heat stress would produce more consistent yields compared to the hybrids that are not tolerant to these stresses. In the 2019 Syngenta Crop Challenge, Syngenta released several large datasets that recorded the yield performances of 2,452 corn hybrids planted in 1,560 locations between 2008 and 2017 and asked participants to classify the corn hybrids as either t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Yang et al (2019) investigated the ability of CNN to estimate rice grain yield using remotely sensed images and found that CNN model provided robust yield forecast throughout the ripening stage. Khaki and Khalilzadeh (2019) used deep CNNs to predict corn yield loss across 1,560 locations in the United States and Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2019) investigated the ability of CNN to estimate rice grain yield using remotely sensed images and found that CNN model provided robust yield forecast throughout the ripening stage. Khaki and Khalilzadeh (2019) used deep CNNs to predict corn yield loss across 1,560 locations in the United States and Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have approached regression problems, in which the response variable is continuous, with machine learning to solve an ecological problem ( James et al., 2013 ). These studies include but not limited to crop yield predictions ( Drummond et al., 2003 ; Vincenzi et al., 2011 ; González Sánchez et al., 2014 ; Jeong et al., 2016 ; Pantazi et al., 2016 ; Cai et al., 2017 ; Chlingaryan et al., 2018 ; Crane-Droesch, 2018 ; Basso and Liu, 2019 ; Khaki and Wang, 2019 ; Shahhosseini et al., 2019c ; Emirhüseyinoğlu and Ryan, 2020 ; Khaki et al., 2020 ), crop quality ( Hoogenboom et al., 2004 ; Karimi et al., 2008 ; Mutanga et al., 2012 ; Shekoofa et al., 2014 ; Qin et al., 2018 ; Ansarifar and Wang, 2019 ; Khaki et al, 2019 ; Lawes et al., 2019 ; Moeinizade et al, 2019 ), water management ( Mohammadi et al., 2015 ; Feng et al., 2017 ; Mehdizadeh et al., 2017 ), soil management ( Johann et al., 2016 ; Morellos et al., 2016 ; Nahvi et al., 2016 ), and others.…”
Section: Introductionmentioning
confidence: 99%
“…The latter have enjoyed wide applications in various ecological classification problems and predictive modeling (Rumpf et al 2010, Shekoofa et al 2014, Crane-Droesch 2018, Karimzadeh and Olafsson 2019, Pham and Olafsson 2019a, 2019b because of their adeptness to deal with nonlinear relationships, high-order interactions and non-normal data (De'ath and Fabricius 2000). Such methods include regularized regressions (Hoerl and Kennard 1970, Tibshirani 1996, Zou and Hastie 2005, tree-based models (Shekoofa et al 2014), Support Vector Machines (Basak et al 2007, Karimi et al 2008, Neural Networks (Liu et al 2001, Crane-Droesch 2018, Khaki and Khalilzadeh 2019, Khaki and Wang 2019 and others.…”
Section: Introductionmentioning
confidence: 99%